PENINGKATAN PERKEMBANGAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL ENGKLEK DI TAMAN KANAK KANAK PATI KEDATON BENGKULU TENGAH - Muryani; Vivi Anggraini; Farida Mayar; Elise Muryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Gross motor skills for early childhood are very important to be stimulated because they greatly support the child's life in the future. The development of gross motor skills is a movement that utilizes the large muscles owned by children for children's activities, one of the games to develop children's large muscles is by using the hopscotch game. The purpose of this study was to see the effect of hopscotch games on the development of gross motor skills of children aged 5-6 years. The study used Classroom Action Research (PTK) with the Kemmis and McTaggart method which consisted of four stages: planning, implementation of actions, observation, and reflection. The research subjects were 14 children, consisting of 5 girls and 9 boys. The study was conducted in two cycles, with data collection techniques through observation, documentation, and tests of gross motor skills. The results showed a significant increase in children's gross motor skills after the hopscotch game was implemented. The average achievement of gross motor skills in cycle I was 2.29 with a percentage of 62% and increased to 3.57 with a percentage of 75% in cycle II. This improvement includes the ability to maintain balance, coordination of movement, leg muscle strength, and accuracy in performing gross motor movements as a whole. Engklek games have been proven to provide effective motor stimulation through a fun, active, and culturally contextual approach. In conclusion, the traditional game of engklek can be used as an effective learning method in developing the physical motor aspects of early childhood. Teachers are encouraged to integrate traditional games into daily learning activities, as a means of developing motor skills while preserving cultural values.